Tom Nook, Capitalist or Comrade? On Nook Discourse and the Millennial Housing Crisis - Vossen, Emma (Loading)

(untitled) (Canadian Game Studies Association, 2020)
Many millennial Animal Crossing players will experience the joy of paying off their beautiful three-floor in-game home only to have that joy cut short by the crushing realization that they may never experience homeownership in real life. Who do we then take that anger and disappointment out on? The capitalists with a stranglehold on the housing market? The governments and companies holding our lives hostage for student loan debt? Our landlords who take most of our income each month so we can keep a roof over our heads? Our bosses who are criminally underpaying us for our labour? Or is it a fictional racoon? Arguments about the ethics of Animal Crossing’s non-playable character Tom Nook are inescapable in online discussions about the Animal Crossing series. These discussions generally have two sides: either Tom Nook is a capitalistic villain who exploits the player’s labour for housing, or he is a benevolent landowner who helps the player out in hard times. Vossen first sets the stage by discussing the cultural significance of both the Animal Crossing series, focusing in on Animal Crossing: New Horizons (2020), and the millennial housing crisis. She then examines the many tweets, memes, comics, and articles that vilify Tom Nook (and a few that defend him) and asks: are we really mad at Tom, or are we mad at the cruelty and greed of the billionaires, bosses, and landowners in our real lives? Vossen argues that what she calls “Nook discourse” represents the radical social potential of Animal Crossing to facilitate large-scale real-world conversations about housing, economic precarity, class, and labour that could help change hearts and minds about the nature of wealth.